2015
DOI: 10.1371/journal.pone.0117518
|View full text |Cite|
|
Sign up to set email alerts
|

SATB1 Overexpression Regulates the Development and Progression in Bladder Cancer through EMT

Abstract: The global gene regulator Special AT-rich sequence-binding protein-1 (SATB1) has been reported to induce EMT-like changes and be associated with poor clinical outcome in several cancers. This study aims to evaluate whether SATB1 affects the biological behaviors of bladder transitional cell carcinoma (BTCC) and further elucidate if this effect works through an epithelial-mesenchymal transition (EMT) pathway. The expression of SATB1, E-cadherin (epithelial markers), vimentin (mesenchymal markers) in BTCC tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 46 publications
2
52
1
Order By: Relevance
“…Previous studies have indicated that SATB1 is associated with prognosis in resected upper gastrointestinal tract adenocarcinoma and other tumor forms (20,23,24). Data from the present study revealed that patients with higher SATB1 mRNA expression had a higher rate of relapse.…”
Section: Discussionsupporting
confidence: 57%
“…Previous studies have indicated that SATB1 is associated with prognosis in resected upper gastrointestinal tract adenocarcinoma and other tumor forms (20,23,24). Data from the present study revealed that patients with higher SATB1 mRNA expression had a higher rate of relapse.…”
Section: Discussionsupporting
confidence: 57%
“…It is already known that SATB1 is an oncogene which promotes breast tumor growth and metastasis [6]; its expression was reported in several breast cancer cell lines and tumor biopsies [7ā€“9]. The association of SATB1 was also observed in several other cancers [9], including colorectal cancer [10ā€“12], prostate cancer [13, 14], endometriod endometrial cancer [15, 16], liver cancer [17], rectal cancer [18], bladder cancer [19], ovarian cancer [20] and gastric cancer [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Notably, we have demonstrated that tumors expressed higher levels of SATB1 metastasized to more lymph nodes, which supports the links between SATB1 and metastasis of OSCC. Indeed, many pieces of researches have reported its proā€metastatic role in various other cancers (Chu et al , ; Han et al , ; Huang et al , ; Mao et al , ; Shen et al , ; Shukla et al , ; Zhang et al , , ; Elebro et al , ; Liu et al , ; Lv et al , ; Wan et al , ). Interestingly, our data have shown that OSCC tumor cells that have migrated to lymph node express even higher levels of SATB1.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggested tumor cells that undergo EMT acquired better survival and metastatic capabilities. A few papers have reported a potential link between SATB1 and the initiation of EMT (Li et al , ; Cheng et al , ; Wan et al , ). In consistent with these findings, our data showed knockdown of SATB1 significantly reduced the expression of EMTā€related proteins, as well as cell invasiveness and motility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation